KARAKTERISTIK DAN MORFOLOGI SPERMATOZOA KEPITING BAKAU (SCYLLA OLIVACEA, HERBEST 1796) - Nuril Farizah (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2011)
Orange mud crab (Scylla olivacea, Herbest 1796) one of the fourth species of mud crab in world. The information of biology reproduction mud crab, specifically for male mud crab is limited. The research aim to study the characteristic and morphology of orange mud crab spermatozoa. Studies were conducted based on the macro and micro morphology of male reproduction Scylla olivacea. Research steps are; 1) Sampling, 2) Collection of testes and spermatozoa, and 3) Preparation scanning electron microscopy (SEM). The result obtained, that male individual have smaller abdomen than female individual and a paired of pleopod as organ ejaculatory. Reproduction system of Scylla olivacea is a paired testis, spermatozoa duct (vasa differentia), and ejaculatory duct. Scylla olivacea, owning spermatozoa flagellate or multistellate, have no midpiece and non-motile. Keywords : mud crab, Scylla olivacea, male, spermatozoa, non-motile